Kecambah: Agen penghidrolisis pati yang potensial - Lina Permatasari (Universitas Mataram, 2022)
Starch is a group of complex carbohydrates containing amylose and amylopectin. Starch can be broken down into simpler molecules such as maltose, isomaltose, and glucose which is called the hydrolysis process. Starch hydrolysis is very useful in several food industries. Enzymatic hydrolysis of starch usually uses the amylase enzyme derived from saliva. However, if you are going to carry out the hydrolysis process on a large scale, it requires large amounts of enzymes. Therefore, this study aimed to examine the ability of enzymes in sprouts to hydrolyze starch and compare it with the ability of starch hydrolysis by saliva and HCl. The isolated sprout samples were added to the starch solution and then incubated at 37oC. Every 5 minutes the mixture was tested qualitatively with Benedict's test and iodine. The same treatment for saliva and HCL. However, HCl was incubated at 100oC. The results of the qualitative test using Benedict's test and the iodine test showed enzymatic process had a higher ability to hydrolyze starch than chemically with HCl. The α-amylase enzyme produced from sprouts showed a higher starch hydrolysis ability than saliva. Sprouts are a natural source that can be developed as a starch hydrolyzing agent.